2021
DOI: 10.1084/jem.20210108
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor immunity in mismatch repair-deficient colorectal cancers requires type I IFN–driven CCL5 and CXCL10

Abstract: Colorectal cancers (CRCs) deficient in DNA mismatch repair (dMMR) contain abundant CD8+ tumor-infiltrating lymphocytes (TILs) responding to the abundant neoantigens from their unstable genomes. Priming of such tumor-targeted TILs first requires recruitment of CD8+ T cells into the tumors, implying that this is an essential prerequisite of successful dMMR anti-tumor immunity. We have discovered that selective recruitment and activation of systemic CD8+ T cells into dMMR CRCs strictly depend on overexpression of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 74 publications
(110 reference statements)
7
69
1
Order By: Relevance
“…The aberrant DNA fragments are spilled over from the nucleus during DNA replication and recognized by cGAS-STING as "non-self" inducing Type I interferon and inflammatory NFkB responses (74,75). In agreement with this hypothesis, recent study by Mowat et al showed that cGAS-STING driven type I interferon signaling is required for CXCL10/ CCL5-dependent T cell recruitment to dMMR tumor site (76). Both "frameshift-neoantigen" and "DNA instability" models are instructive and complementary in explaining the origins of the dMMR tumor immunogenicity (Figure 1C).…”
Section: Msi-h Cancer and Clinical Managementmentioning
confidence: 78%
“…The aberrant DNA fragments are spilled over from the nucleus during DNA replication and recognized by cGAS-STING as "non-self" inducing Type I interferon and inflammatory NFkB responses (74,75). In agreement with this hypothesis, recent study by Mowat et al showed that cGAS-STING driven type I interferon signaling is required for CXCL10/ CCL5-dependent T cell recruitment to dMMR tumor site (76). Both "frameshift-neoantigen" and "DNA instability" models are instructive and complementary in explaining the origins of the dMMR tumor immunogenicity (Figure 1C).…”
Section: Msi-h Cancer and Clinical Managementmentioning
confidence: 78%
“…Treatment-driven ICD involves the activation of a cancer cell-intrinsic type I IFN response and consequent secretion of CXCL10 that mediates chemotactic effects of activating immune cells, including cytotoxic CD8+ T-cells and NK-cells, into the tumor microenvironment [ 19 , 45 ]. Given that CXCL10 expression by tumors is associated with effective anti-tumor immunity and CD8+ T-cell regulation [ 46 ], we did not expect to observe a negative correlation between circulating levels of CXCL10 and PFS in patients with stage I NSCLC treated with SBRT. However, in line with our observations, previous studies have also shown similar results in patients with other cancer types; high levels of CXCL10 were correlated with tumor recurrence or even a lower survival [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 96%
“…Although it was initially thought that type I IFNs exert direct anticancer effects by activating IFNAR signaling in malignant cells hence inhibiting cell cycle progression 100 , promoting terminal differentiation 101 or inducing apoptosis 102 , it is becoming increasingly clear that type I IFNs mainly function by stimulating anticancer immune responses via autocrine or paracrine signaling circuits by IFN-stimulated genes 103,104 . These have an instrumental role in the production of IFN-dependent chemokines that lead to preferential recruitment and retention of systemic CD8 + T cells in the tumor, an outcome that can be recapitulated by treatment with type I IFN or DNA damaging chemo-and radiotherapies 105 . In our work, we found that SHP-2 deficient TAMs displayed a significant increase of STING (Supplementary Table 2), TLR signaling (Fig.…”
Section: Discussionmentioning
confidence: 99%